Why I Can’t Love the Homemade Semantic Web - Bengtson, Jason A. (My University, 2011)
Almost all information professionals agree that the web needs to move to a semantic structure. While work is proceeding in this area, movements to get individual web authors to use semantic markup tools have also been on the rise. This author argues that such efforts are ill conceived and he proposes an automated alternative.
Citation: Bengtson, Jason. "Why I Can't Love the Homemade Semantic Web." B Sides Jan (2010) : n. pag. Web.
Keywords: Semantic; Web; Internet; Search; Data; Mining